Odpowiedzi

2010-02-16T15:05:59+01:00
A)x+1+x+4=
2x+5


b)2(2x+3)(2x-1)=
4x+6+2x-1=
6x+5
c)-(z+7)(x-3)=-z-7+x-3=-10
d)1-(z+5)(z-1)=1-z-5+z-1 =5
Najlepsza Odpowiedź!
2010-02-16T15:47:18+01:00
A) (x+1)(x+4)=x²+4x+x+4=x²+5x+4
b) 2(2x+3)(2x-1)=2(4x²-2x+6x-3)=2(4x²+4x-3)=8x²+8x-6
c) -(z+7)(x-3)=-(zx-3z+7x-21)=-zx+3z-7x+21
d) 1-(z+5)(z-1)=-(z²-z+5z-5)=-(z²+4z-5)=-z²-4z+5
e) 2k²-(k+3)(2k-4)=2k²-(2k²-4k+6k-12)=2k²-(2k²+2k-12)=2k²-2k²-2k+12=-2k+12
f) -3(a+2b)(a-b)+3a²=-3(a²-ab+2ab-2b²)+3a²=-3(a²+ab-2b²)+3a²=-3a²-3ab+6b²+3a²=-3ab+6b²